Achados radiológicos pulmonares das principais micoses em pacientes imunocompetentes - Ferrari, Rodrigo dos Santos (2014)
Introduction: paracoccidioidomycosis (PCM), histoplasmosis and cryptococcosis are mycoses caused by dimorphic fungi which exist as yeasts or spherules in the tissues. The infection occurs when the fungus is inhaled, involving mainly the lungs. Justification: These disorders are relatively common in the immunocompetent population, and are an important cause of radiological abnormalities on chest computed tomography scans (CT / HRCT). Objectives: To identify and describe the frequency of radiological findings of PCM, histoplasmosis and cryptococcosis on CT/HRCT scans of the thorax through the analysis of imaging studies and medical records of immunocompetent patients diagnosed with these pathologies at the University Hospital of Santa Maria (HUSM) from January 2006 to April 2012. Materials and methods: Transversal study which were evaluated CT / HRCT scans of the chest and the medical records of patients hospitalized and/or receiving outpatient treatment in the HUSM between January 2006 to April 2012. Results: The study population was formed by 28 patients, 21 men and 7 women, aged between 18 and 75 years. The PCM was found in 60% of cases and their radiological findings were as: inter / intralobular septal thickening and / or nodules (76,4%), lung parenchymal interstitial thickening and/or architectural distortion (58,8%), bronchial wall thickening and / or ground-glass opacities (52,9%), consolidation and / or parenchymal bands (41.1%), cavitated lesions (35,3%), reversed halo sign (23,5%), areas of cicatricial enfhysema (17,7%) and lung mass (5,9%). Cryptococcosis it was observed: lung nodules and / or cavitated lesions (50,0%), consolidation and / or hilar lymphadenomegaly (37,5%), lung mass (25,0%), pleural effusion, ground-glass opacities and / or mediastinal lymphadenomegaly (12,5%). Histoplasmosis in the most frequent findings were signs of emphysema and / or pulmonary fibrosis (66,6%), bullous areas and / or architectural distortion (66,6%). Conclusion: PCM, histoplasmosis and cryptococcosis are a frequent cause of radiological abnormalities on CT/HRCT scans of the thorax. Therefore, it is important to recognize these findings so that we can include these diseases in the differential diagnosis of pulmonary lesions.